2021
DOI: 10.3390/met11060920
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependent Stress–Strain Behavior and Martensite Stabilization in Magnetic Shape Memory Ni51.1Fe16.4Ga26.3Co6.2 Single Crystal

Patricia Lázpita,
Elena Villa,
Francesca Villa
et al.

Abstract: The superelastic properties and stress-induced martensite (SIM) stabilization have been studied in a shape memory Ni51.1Fe16.4Ga26.3Co6.2 single crystal. The single crystal, characterized by a thermally induced forward martensitic transformation temperature around 56 °C in the initial state, has been submitted to compression mechanical testing at different temperatures well above, near and below the martensitic transformation (MT). After each mechanical test, the characteristic MT temperatures and the transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
0
8
1
Order By: Relevance
“…In fact, the above martensite stabilization is similar to the effect of the so-called SIM aging, where the stabilization is achieved by aging under uniaxial stress after the formation of stress induced martensite [11][12][13][14][15][16][17][18]. While the SIM aging effect is well interpreted by the symmetry confirming short range ordering [14,19,20], the interpretation of the anomalous shape of the stress-strain curves and the burst-like strain recovery still is in infancy [1,3,4,9] and mostly qualitative arguments were offered. There are only few articles in which more quantitative treatment can be found from two groups [1,3,[21][22][23].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…In fact, the above martensite stabilization is similar to the effect of the so-called SIM aging, where the stabilization is achieved by aging under uniaxial stress after the formation of stress induced martensite [11][12][13][14][15][16][17][18]. While the SIM aging effect is well interpreted by the symmetry confirming short range ordering [14,19,20], the interpretation of the anomalous shape of the stress-strain curves and the burst-like strain recovery still is in infancy [1,3,4,9] and mostly qualitative arguments were offered. There are only few articles in which more quantitative treatment can be found from two groups [1,3,[21][22][23].…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, the strain recovery of the stress induced martensite to austenite during heating can be very fast (burst-like recovery). For instance, it was observed that the DSC peak of this recovery was only about 10 −3 -10 −5 degree wide (instead of the usual 1-50 K wide transitions at typical 1-10 K/min rates) and was accompanied with jumping of the sample as well as with audible click [1][2][3][4][5][6][7][8][9][10]. In addition, the DSC peak appeared at higher temperature (by 10-60 K higher) than the corresponding peak of the reverse transformation measured after thermally induced cycling.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations